Nature-inspired computing and optimization : theory and applications - Patnaik, Srikanta; Yang, Xin-She; 中松, 和巳 (Modeling and Optimization in Science and Technologies, 2017)
The text provides readers with a snapshot of the state of the art in the field of nature-inspired computing and its application in optimisation. The approach is mainly practice-oriented: each bio-inspired technique or algorithm is introduced together with one of its possible applications.